The utilization of the partograph by midwives in Lebowakgomo and Zebediela Level 1 hospitals in Capricorn district, Limpopo Province, South Africa - Shokane, M. A.; Thopola, M. K.; Jali, M. N.; Kgole, J. C.; Mamogobo, M. P. (My University, 2013)
The purpose of this study was to evaluate the utilization of the partograph by midwives when monitoring pregnant women in labour wards of the Lebowakgomo and Zebediela level 1 hospitals in the Capricorn District in Limpopo Province, South Africa. A qualitative, descriptive, explorative and contextual research design was used. The population included 34 midwives registered with the South African Nursing Council (SANC) and who are practicing as such in Lebowakgomo and Zebediela level 1 hospitals. A purposive sampling technique was used to select 15 participants. Data were collected using semi-structured in–depth interviews. Data were analyzed qualitatively by means of the open coding methods and four themes emerged, namely, monitoring and plotting of foetal status during the intrapartum phase, monitoring and documenting the progress of labour during the intrapartum phase, monitoring and plotting maternal status during intrapartum phase and lack of human resources. The study found that midwives were failing to monitor and to plot the foetal status correctly during the latent phase of labour and also the latent phase of the progress of labour. The study also revealed staff shortage in labour wards which made it difficult for midwives to provide quality midwifery care through the utilization of the partgraph.
Published in: African Journal for Physical, Health Education, Recreation and Dance (AJPHERD), March 2013 (Supplement 1), pp. 159-168.
Keywords: Intrapartum; Midwifery care; Partograph; Midwifery